The Blocking Mechanism of the Vertical Feeding System of Roadside Support Body Material for Backfilling Gob-Side Entry Retaining - Peng Gong; Zhanguo Ma; Jian Sun; Ray Ruichong Zhang (Advances in Civil Engineering)
Reliable operation of the feeding system plays a crucial role in ensuring the safe and efficient production of the working face of backfilling gob-side entry retaining (GER). In the process of vertical feeding of the roadside support body material, the problem of blocking of the feeding shaft has occurred to the test mine, which seriously affects the production safety in mines. In this paper, based on the theoretical analysis, a fluid-solid coupling numerical model was established. The change rules of the speed of sacked gangue, pressure of air below it, and speed vector distribution with different vent diameters were obtained. The blocking mechanism of the feeding system was revealed. The results show that if the exhaust vent of the stock bin was shut, the speed of gangue in the mine increased and then decreased and finally blocked in the feeding shaft. If the exhaust vent of the stock bin was opened for pressure discharge, with the increase of diameter of the exhaust vent, the maximum speed and ending speed of sacked gangue increased, pressure differential reduced, and speed vector was uniformly distributed. The energy criterion of blocking of the feeding shaft was further obtained. Based on the engineering conditions of the test mine, when the feeding shaft is blocked, the critical value of diameter of the exhaust vent is 30 mm. The research results provide basis for the design of key parameters of the vertical feeding system, ensuring the safe and efficient production of gob-backfilled GER working face.